TRENDS IN THE DEVELOPMENT OF INVESTMENT RELATIONS BETWEEN THE REPUBLIC OF ARMENIA AND THE RUSSIAN FEDERATION - H. O. Avetisyan (Модернизация, инновация, развитие, 2015)
The paper presents the results of research investment relations betweenArmeniaandRussiain 2000–2012. It is anaysed the operation results of the largest companies inArmeniawith Russian capital.